(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVES: to evaluate the renal function of patients in an intensive care unit, to identify the predisposing factors for the development of renal failure, and to develop an algorithm to help in the control of the disease. METHOD: exploratory, descriptive, prospective study with a quantitative approach. RESULTS: a total of 30 patients (75.0%) were diagnosed with kidney failure and the main factors associated with this disease were: advanced age, systemic arterial hypertension, diabetes mellitus, lung diseases, and antibiotic use. Of these, 23 patients (76.6%) showed a reduction in creatinine clearance in the first 24 hours of hospitalization. CONCLUSION: a decline in renal function was observed in a significant number of subjects, therefore, an algorithm was developed with the aim of helping in the control of renal failure in a practical and functional way.